Validity and reliability of fluoroscopy for digital radiography: a new way to evaluate diaphragmatic mobility - Bruna Estima Leal; Márcia Aparecida Gonçalves; Liseane Gonçalves Lisboa; Larissa Martins Schmitz Linné; Michelle Gonçalves de Souza Tavares; Wellington Pereira Yamaguti; Elaine Paulin (BMC Pulmonary Medicine, 2017)
Abstract Background Fluoroscopy is considered the most accurate method to evaluate the diaphragm, yet most existing methods for measuring diaphragmatic mobility using fluoroscopy are complex. To assess the validity and reliability of a new evaluation method of diaphragmatic motion using fluoroscopy by digital radiography of healthy adults. Methods Twenty-six adults were evaluated, according to the parameters: anthropometry and pulmonary function test. The evaluation of diaphragm mobility by means of fluoroscopy by digital radiography method was randomly conducted by two raters (A and B). The Pearson correlation coefficient and the intraclass correlation coefficient (ICC) were used to assess the concurrent validity. The inter-rater and intra-rater reliability of the measurement of diaphragmatic motion was determined using ICC and a confidence interval of 95%. Results There was a relationship in the assessment of the concurrent validity. There was good inter-rater reliability for right hemidiaphragm mobility and moderate reliability for left hemidiaphragm in the first assessment. In the second assessment, there was good reliability for the mobility of both hemidiaphragms. There was good intra-rater reliability in the mobility of both hemidiaphragms for raters A and B. Conclusion The evaluation of diaphragmatic motion using fluoroscopy by digital radiography proved to be a valid and reliable method of healthy adults.